2022
DOI: 10.1111/bcpt.13795
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol attenuated atrophy of C2C12 myotubes induced by tumour‐derived exosomal miR‐183‐5p through inhibiting Smad3 pathway activation and keeping mitochondrial respiration

Abstract: Cancer-derived exosomes are involved in the development of cancer cachexia.Carnosol, which exhibited ameliorating effects on cancer cachexia of C26 tumour-bearing mice in our previous study, alleviated atrophy of C2C12 myotubes induced by exosomes of C26 tumour cells in the present study. MiR-183-5p was found to be rich in C26 cells and C26 exosomes, and miR-183-5p mimic could directly induce atrophy of C2C12 myotubes. Carnosol at 5 to 20 μM could dose-dependently ameliorate the myotube atrophy induced by miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…The reason is that the levels of miR‐195a‐5p and miR‐125b‐1‐3p in C26 EVs were much higher than those in MC38 EVs, as confirmed by miRNA‐seq data 48 . In another study, the same group reported another colon cancer cell‐derived EV‐associated miRNA named miR‐183‐5p could also induce myotube protein degradation 49 . By targeting FHL1, miR183‐5p activates the myostatin/Smad3 pathway, thus promoting muscle proteolysis mediated by Atrogin‐1 and MuRF‐1, canonical regulators of the ubiquitin‐proteasome pathway 49 .…”
Section: The Biological Regulation Of Ev Cargoes In Skeletal Muscle W...mentioning
confidence: 85%
See 1 more Smart Citation
“…The reason is that the levels of miR‐195a‐5p and miR‐125b‐1‐3p in C26 EVs were much higher than those in MC38 EVs, as confirmed by miRNA‐seq data 48 . In another study, the same group reported another colon cancer cell‐derived EV‐associated miRNA named miR‐183‐5p could also induce myotube protein degradation 49 . By targeting FHL1, miR183‐5p activates the myostatin/Smad3 pathway, thus promoting muscle proteolysis mediated by Atrogin‐1 and MuRF‐1, canonical regulators of the ubiquitin‐proteasome pathway 49 .…”
Section: The Biological Regulation Of Ev Cargoes In Skeletal Muscle W...mentioning
confidence: 85%
“…And it was found that skeletal muscle wasting could also be induced by angiotensin II, so the FDA‐approved drug losartan could be used to provide protection against muscle wasting 77,78 . Carnosol, an active component of the herbal medicine rosemary, has the ability to attenuate muscle loss induced by EVs 49 . Glycyrrhizin, an inhibitor of HMGB1, can be used as a potential drug to alleviate muscle wasting 57 .…”
Section: Therapeutic Implications Of Extracellular Vesicles In Skelet...mentioning
confidence: 99%
“…Additionally, tumor-derived EVs can exacerbate cachexia by sending pro-cachectic signals to distant tissues. Therapeutically, targeting these tumor-derived EVs [ 198 201 ] or blocking their pathway activation [ 43 , 56 , 67 ] can mitigate cachexia-related complications. For example, amiloride, a commonly used diuretic, significantly improves metabolic disorders in cachectic gastrocnemius by effectively inhibiting tumor-derived exosome release, thus affecting muscle catabolism, protein synthesis, glycolysis, and ketone body oxidation [ 201 ].…”
Section: Evs As Therapeutic Agents Of CCmentioning
confidence: 99%
“…An enrichment of miR-183-5p was observed in C26 cells and C26 exosomes. Furthermore, the induction of muscle duct atrophy in C2C12 cells by miR-183-5p mimics was accompanied by increased expression of Atrogin-1, MuRF-1, myostatin, HIF-1α, p-SMAD3, and p-STAT3, along with decreased mitochondrial respiration [ 97 ]. Four and a half LIM domain protein 1 (FHL1) plays a role in muscle growth, differentiation, and myomas formation, and it is also recognized as a regulator of skeletal muscle mass.…”
Section: Cancer Cell-derived Exosomes Promote the Formation Of Cancer...mentioning
confidence: 99%
“…Additionally, FHL1 gene has been identified as a direct target of miR-183-5p. By reducing the expression of Atrogin-1, MuRF-1, and myostatin, inhibiting the activation of the Smad3 pathway, and preserving the mitochondrial respiration, Carnosol has a protective effect on mir-183-5p-induced muscular tube atrophy of C2C12 cells [ 97 ].…”
Section: Cancer Cell-derived Exosomes Promote the Formation Of Cancer...mentioning
confidence: 99%